KESENJANGAN IMAN DAN PRAKTIK ETIKA WAKTU ISLAM DALAM INSTITUSIONALISASI PERILAKU MASYARAKAT MULTIKULTURAL - Moh . Nadhif; Moh. Subthi Buchori; Rifqi Abqoriya; Ahmad Naweed Rahimi Khamosh; Ouail Brahim Sabri (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study examines the faith-practice gap in Islamic time ethics by explaining why values such as punctuality, commitment, amanah, and accountability, although strongly emphasized in Islamic teaching, are not always translated into consistent time-discipline behavior. Using an explanatory sequential mixed-methods design, the study analyzes survey data from 356 professionals in Muslim and Western organizational contexts and deepens the interpretation through semi-structured interviews. The quantitative phase uses PLS-SEM to test the effects of Islamic Temporal Ethics on moral internalization, institutionalization, and time-discipline behavior, while the qualitative phase explores how respondents interpret religious language, organizational rules, and multicultural time norms. The findings show that Islamic Temporal Ethics strengthens both moral internalization and institutionalization, yet its effect on time-discipline behavior operates mainly through these two mechanisms. Institutionalization appears more decisive than internalization because rules, sanctions, routines, and accountability systems stabilize ethical behavior beyond personal intention. Multicultural context moderates the process: monochronic and institutionally tight environments are more effective in transforming ethical values into visible practice. The article proposes Islamic Temporal Ethics Decoupling as a sociological concept for understanding the gap between religious ideals and everyday conduct.